2017
DOI: 10.18632/oncotarget.21092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of acute myocardial infarction in young smokers and non-smokers (≤ 45 years): a systematic review and meta-analysis

Abstract: The effect of smoking on the prognosis of young patients with acute myocardial infarction (AMI) is inconclusive. We enrolled 2188 young AMI patients (≤ 45 years) from the cardiac center of the Chinese PLA General Hospital and Anzhen Hospital and analyzed their clinical characteristics and prognosis. We also searched the PubMed, EMBASE, and Cochrane Central Register of Controlled Trials electronic databases for January 2001 to March 2017 and considered for inclusion in a meta-analysis those clinical trials that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
11
0
3
Order By: Relevance
“…Similarly, in-hospital outcomes such as post-procedure no-reflow, acute stent thrombosis, and mortality were similar for smoker and non-smoker sub-groups. Our study findings are aligned with the finding of a systematic review and meta-analysis conducted by Liu et al [9]. But persistent smoking after revascularization is an independent predictor of long-term reoccurrence of major adverse cardiac events (MACE) [13,14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, in-hospital outcomes such as post-procedure no-reflow, acute stent thrombosis, and mortality were similar for smoker and non-smoker sub-groups. Our study findings are aligned with the finding of a systematic review and meta-analysis conducted by Liu et al [9]. But persistent smoking after revascularization is an independent predictor of long-term reoccurrence of major adverse cardiac events (MACE) [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…According to the World Health Organization (WHO), global annual deaths attributable to cardiovascular diseases (CVD) are around 17.9 million, and more than 75% of these cases are from developing countries [7]. CADs are considered to be the disease of old age, unfortunately, the incidence of CAD is increased among the younger population [8,9]. A local study reported cigarette smoking as the second most prevalent CVD risk factor, after increased BMI, among young (<45 years) patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…2 The burden of cardiovascular disease is a significant public concern. 3 According to Nowbar et al 4 ischemic heart disease (IHD) is the prime cause of death as it caused around 9 million deaths in 2016. 5 A report issued by the American Heart Association mentioned that approximately 17.9 million people die from heart disease that represents 31% of the total deaths in the Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The major causes of cardiovascular disease are smoking, reperfusion therapy, and left ventricular ejection fraction. 3 The Institute for Health Metrics and Evaluation (IHME) 11 stated that the prevalence of IHD in Jordan accounts for 54.7 of the annual deaths. Eshah 12 has reported a substantial lacking public awareness about IHD lead towards increased IHD related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that elderly individuals are the main population with a high AMI incidence (7), this reduced incidence as mentioned above was a delightful change. Yet, the incidence of AMI among the young population has gradually shown a rising trend (6,8,9). The young population who suffers AMI can show many clinical symptoms, such as ischemic chest pain, and the clinical course is extremely short.…”
Section: Introductionmentioning
confidence: 99%